Redes sociais virtuais em questão: uma análise das páginas no facebook dos agentes políticos em Sant'ana do Livramento - (:unkn) unknown (Universidade Federal do Pampa, 2019)
Social media has gained prominence in the political environment in recent times, with the evolution of digital platforms and expansion of their access have become fundamental tools as a means of electora lpropaganda and the approach of political agents to their public.Thus,this article, in a qualitative and quantitative research, aims to analyze the relationship of the councilors of the municipality of Sant'Ana do Livramento with their main official profile son the Facebook platform. The study consists in exploring the 14 digital profiles of the political agents available through data collection and analysis of the content exposed in the publications between 2016, 2017 and 2018. The publications were classified in democratic values ​​based on the Castro and Corso model (2017) in: Transparency, Accountability, Services, Participation, Advertising and Others. The research found that despite the particularities of each agent within their profile, the value Others prevails in the publications analyzed, which shows a lack of exposure of government actions of political agentsinsocial networks.
Keywords: Gestão pública; Governo municipal; Redes sociais; CNPQ::CIENCIAS SOCIAIS APLICADAS